2020
DOI: 10.21203/rs.2.17169/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Functional Outcomes and Complications of Different Reconstruction Methods for Giant Cell Tumor of the Distal Radius: Comparison of Osteoarticular Allograft and Three-Dimensional-Printed Prosthesis

Abstract: Background: En bloc excision has been increasingly used for the management of giant cell tumors(GCTs) in the distal radius. An osteoarticular allograft has been used extensively for decades, and custom-made prosthesis reconstruction has been more recently applied. We aimed to compare the clinical outcomes of the two procedures. Methods: We retrospectively analyzed 30 patients with Campanacci III or recurrent GCTs of the distal radius for follow-up at a mean of 33.2 months. In total, 15 underwent osteoarticula… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…According to some authors, osteoarticular allograft reconstruction is a long-lasting but still temporary solution before performing megaprosthesis. 3,19 Although distal tibial reconstruction using osteoarticular allografts can offer acceptable functional results, reconstruction using a custom-made titanium bone replacement system (MUTARS) gives early function recovery, allows to preserve ankle motion, and provides proper oncologic treatment. 1,2,12,17,21 Additionally, in young patients, the expandable system allows to expand the length of the limb.…”
Section: Discussionmentioning
confidence: 99%
“…According to some authors, osteoarticular allograft reconstruction is a long-lasting but still temporary solution before performing megaprosthesis. 3,19 Although distal tibial reconstruction using osteoarticular allografts can offer acceptable functional results, reconstruction using a custom-made titanium bone replacement system (MUTARS) gives early function recovery, allows to preserve ankle motion, and provides proper oncologic treatment. 1,2,12,17,21 Additionally, in young patients, the expandable system allows to expand the length of the limb.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its benign label, the distal radius is the most common primary site responsible for metastases and a high focus on ruling out pulmonary metastasis is mandatory in the pre-operative assessment [9,10,12,19] . In well-marginated cortical borders, curettage with bone grafting/cement packing is acceptable despite the recurrence rates up to 50% [4,5,7,17,19] . Campanacci grade, pathological fractures, tumor site, and adjuvant therapy are recognized predictors of local recurrence [1,19] .…”
Section: Discussionmentioning
confidence: 99%
“…Giant cell tumor of bone (GCTB) is a benign but locally aggressive intramedullary bone tumor that was first described in 1818 by Cooper and Travers [1][2][3] . The distal radius is the third most common site of GCTB after distal femur and proximal tibia [1,[4][5][6][7] . Local recurrences occur in 70% of the cases within 24 months after excision and lung metastasis in 2% of the patients [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…The present study reported a case of wrist preservation surgery using a 3D-printed custom-made porous endoprosthesis after en bloc resection of the EHE in the distal radius. 3D-printed custom-made porous endoprosthesis is a novel uncemented implant that has demonstrated great clinical success in the reconstruction of extensive bone defects (9)(10)(11). Due to its optimized-fit shape and porous surface, it was considered a feasible alternative for the massive defect of the distal radius to preserve the intact wrist.…”
Section: Introductionmentioning
confidence: 99%